Flood Tidal Inundation Vulnerability Level in Pekalongan City, Central Java, Indonesia - Ilyas, Tasya Annisa Ramadanti; Kurniawan, Imam Alfagan; Utami, Aulia Rahma; Ardiansyah, Muhammad Farrel; Jalaluddin, Muzani (Universitas Lampung, 2025)
Pekalongan City, located on the northern coast of Java Island, frequently experiences flooding caused by rainfall and tidal inundation due to its proximity to the sea and low elevation. These conditions make Pekalongan a high-risk area, particularly as the community remains highly vulnerable to both types of flooding. Recurrent flood events in the city have caused extensive damage to houses and public facilities, leading to considerable economic losses. This study aims to assess the level of flood vulnerability in Pekalongan City using the National Disaster Management Agency (BNPB) Regulation No. 2 of 2012 as the primary framework. The analysis relied on secondary data obtained from previous studies, relevant institutions in Pekalongan, and official government sources. The findings reveal that Pekalongan City remains highly vulnerable to flooding, with significant risks of losses recurring in every flood event. Index-based assessments indicate that the highest levels of vulnerability are found in the economic and physical dimensions, while environmental and social vulnerabilities are categorized as moderate. These results underscore the urgent need for strategic interventions by both the government and local communities to strengthen adaptive capacity and enhance resilience against the increasing frequency and intensity of flood hazards.